Co-delivery of two anti-HIV drug nanocrystals from electrospun nanofibers - Malta, Rafaela (2017)
TRUVADA is the only medication approved by FDA for pre-exposure prophylaxis of the HIV infection. They are tablets with fixed dosages of two antiretroviral compounds for daily oral uptake: Tenofovir disoproxil fumarate (TDF) and Emtricitabine (EMT) that are reverse transcriptase inhibitors. Objectives:  Incorporate TDF and EMT drugs in polymeric nanofibers produced by electrospinning; chosen polymers were polyoxyethilene (PEO) and polycaprolactone (PCL). Characterize the nanofibers and study the in vitro release profile of the drugs. Evaluate the possibility of a topical administration of the loaded fibers , by rectal or genital route, for HIV infection prophylaxis.